PENGARUH ELEMEN-ELEMEN CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Febriana, Ester Ayu; Halim, Abdul; Sari, Ati Retna (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2019)
The purpose of this study is to analyze the influence of elements of Corporate Governance (CG) on the extent of Corporate Social Responsibility (CSR) disclosure in banking companies listed on the IDX and identify the factors that influence companies to conduct disclosure of Corporate Social Responsibility (CSR). The elements of Corporate Governance in this study consist of managerial ownership, institutional ownership, audit committee, board of commissioners size, independent board of commissioners and audit quality. The results of the hypothesis test indicate that the Corporate Governance (GCG) variable significantly influences the disclosure of Corporate Social Responsibility (CSR) on banking companies listed on the IDX. These results can be proven by the results of hypothesis testing which results in Corporate Governance criteria consisting of managerial ownership, institutional ownership, audit committee, board of commissioners, independent board of commissioners and audit quality simultaneously having a significant effect on the disclosure of Corporate Social Responsibility (CSR) in the company banking registered on the IDX. While partially only institutional ownership and audit quality do not significantly influence the disclosure of Corporate Social Responsibility (CSR) in pharmaceutical sub-sector companies listed on the IDX.